Local adaptation in populations of Mycobacterium tuberculosis endemic to the Indian Ocean Rim[version 1; peer review: 3 approved] - Menardo, F.; Rutaihwa, L.K.; Zwyer, M.; Borrell, S.; Comas, I.; Conceição, E.C.; Coscolla, M.; Cox, H.; Joloba, M.; Dou, H.; Feldmann, J.; Fenner, L.; et al. (F1000Research, 2021)
Background: Lineage 1 (L1) and 3 (L3) are two lineages of the Mycobacterium tuberculosis complex (MTBC) causing tuberculosis (TB) in humans. L1 and L3 are prevalent around the rim of the Indian Ocean, the region that accounts for most of the world’s new TB cases. Despite their relevance for this region, L1 and L3 remain understudied. Methods: We analyzed 2,938 L1 and 2,030 L3 whole genome sequences originating from 69 countries. We reconstructed the evolutionary history of these two lineages and identified genes under positive selection. Results: We found a strongly asymmetric pattern of migration from South Asia toward neighboring regions, highlighting the historical role of South Asia in the dispersion of L1 and L3. Moreover, we found that several genes were under positive selection, including genes involved in virulence and resistance to antibiotics . For L1 we identified signatures of local adaptation at the esxH locus, a gene coding for a secreted effector that targets the human endosomal sorting complex, and is included in several vaccine candidates. Conclusions: Our study highlights the importance of genetic diversity in the MTBC, and sheds new light on two of the most important MTBC lineages affecting humans.
Research Article
Keywords: Mycobacterium tuberculosis; adaptation; coevolution